Cytokeratin expression in plasmablastic lymphoma – a possible diagnostic pitfall in the routine work‐up of tumours. Issue 6 (25th December 2020) - Huettl, Katrin S; Staiger, Annette M; Horn, Heike; Frontzek, Fabian; Goodlad, John R; Tapia, Gustavo; Rosenwald, Andreas; Klapper, Wolfram; Fend, Falko; Climent, Fina; Castellvi, Josep; Tzankov, Alexandar; et al.
Abstract : Aims: Plasmablastic lymphoma (PBL) is a rare aggressive B‐cell lymphoma that frequently arises at extranodal sites in the setting of immunosuppression. The diagnosis of PBL is complex, owing to a frequent solid or cohesive growth pattern, and an often unusual immunophenotype. Several case reports have described cytokeratin (CK) expression in PBL, introducing a diagnostic pitfall. The aim of this study was to determine the frequency of CK expression in PBL in the largest series available to date. Methods and results: By using immunohistochemistry in a cohort of 72 PBLs, we identified CK8/18 positivity in 11 of 72 cases (15%) and AE1/3 positivity in six of 65 cases (9%), clearly contrasting with a control series of non‐PBL aggressive B‐cell lymphomas (one of 96 diffuse large B‐cell lymphomas), as well as with data in the literature describing only occasional CK expression in haematological neoplasms. Conclusions: Our data indicate CK expression in a substantial number (15%) of PBLs. In view of the particular morphological features of PBL and its frequent negativity for the common leukocyte antigen and B‐cell markers, this feature represents a pitfall in the routine diagnostic work‐up of PBL, and requires more extensive immunohistochemical and molecular characterisation of cases entering the differential diagnosis. Abstract :